Representation of Social Actors in Sexual Violence Issue in The New York Times and The Jakarta Post Newspapers: A Critical Discourse Analysis - Widya Evayani; Akhyar Rido (TEKNOSASTIK, 2019)
Sexual violence was a social issue that arises comprehensive responses and can happen to all layers of society regardless of position, age, or other social factors. The objective of this study is to reveal how social actors are represented in news reporting of sexual violence. The data were collected from the official website of The Jakarta Post and The New York Times. The findings show that to detach the actor (exclusion), both of newspaper mostly presented the actor especially the victim as a passive agent and the perpetrator as an active agent. The salient differences were found in the use of inclusion strategy. This confirms that The Jakarta Post presented the actor as specific individual such as by their gender, age, and occupation while The New York Times presented them by their surname and title such as “Professor”.Keywords: exclusion, inclusion, sexual violence, social actor